Aplikasi Metode Akustik untuk Uji Kesegaran Ikan - Indra Jaya; Dewi Kartika Ramadhan (Jurnal Pengolahan Hasil Perikanan Indonesia, 2006)
This paper describes an attempt to introduce acoustic method as an alternative for measuring fish freshness. The method was first tested and compared to the conventional and well accepted method, such as organoleptic, TVB, TPC and pH. The test was carried out by direct comparison between the acoustic measurements with the conventional one on Pangasius sp for the 24 hours period after the fish is killed. The test results show that there is a good qualitative agreement between the two methods, where the degradation of fish quality can be differentiated clearly as a function of time. Thus the attempt to introduce acoustic method as an alternative technique for measuring fish freshness is promising and encouraging.Keywords: fish freshness, acoustic method